An investigation of the regulation and physiological role of Listeria monocytogenes extracellular polymer - Wong, Ho Ting Lawrence (2013)
It was shown that Listeria monocytogenes cells grown in a defined minimal, MCDB202, showed enhanced extracellular polymeric substances production compared to BHI. On the other hand, it was reported that in L. monocytogenes luxS mutant, AI-2 reduction and biofilm enhancement were seen. It is hypotheses that there could be a linkage between the AI-2 signaling system and the EPS formation. The expression of EPS could be induced by the reduction in AI-2.